Rovibrationally resolved photodissociation of SH+. (4th April 2016) - McMillan, E C; Shen, G; McCann, J F; McLaughlin, B M; Stancil, P C
Abstract: Photodissociation cross sections for the SH + radical are computed from all rovibrational (RV) levels of the ground electronic state X 3 Σ − for wavelengths from threshold to 500 Å. The five electronic transitions, 2 3 Σ − ← X 3 Σ −, 3 3 Σ − ← X 3 Σ −, A 3 Π ← X 3 Σ −, 2 3 Π ← X 3 Σ −, and 3 3 Π ← X 3 Σ −, are treated with a fully quantum–mechanical two-state model, i.e. nonadiabatic couplings between excited states were not included. The photodissociation calculations incorporate adiabatic potentials and transition dipole moment functions computed in the multireference configuration interaction approach along with the Davidson correction (MRCI+Q), but adjusted to match available experimental molecular data and asymptotic atomic limits. Local thermodynamic equilibrium (LTE) photodissociation cross sections were computed which assume a Boltzmann distribution of RV levels in the X 3 Σ − molecular state of the SH + cation. The LTE cross sections are presented for temperatures in the range 1000–10 000 K. Applications of the current photodissociation cross sections to interstellar gas, photon-dominated regions, and stellar atmospheres are briefly discussed.